JENIS-JENIS IKAN DI PERAIRAN ESTUARIA TAMAN NASIONAL SEMBILANG - Suryanto Adi Wardoyo; Muhammad Iqbal (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2003)
Sembilang National Park is a mangrove forest functioned as habitat of important fishes for fisherman. Study on fishes species lived in Sembilang National Park was done in March and June 2001, by survey method and identification of fish caught by fisherman using tugik, belat kelong, jarring sondong, jarring kantong, jarring cawing and pancing rawai. Fish catch was consisted of 75 species deriving from 14 ordo and 54 familiy and mostyly dominated by marine species. Freshwater species found was only 14 species. Water quality parameters varied from the upper to the down stream with salinity, temperature and pH ranged from 0-26%, 25-30°C and 2,0-7,7, respectively. High tide and rainfall also affected the distribution of the fish and water quality. In addition to high tide, fish distribution influenced by types and capacity of fishing gear, adjusted according to environment condition in mangrove zone, used by the fisherman.Keywords : fish, National Park Sembilang, Mangrove